A narrative review on female physique athletes: The physiological and psychological implications of weight manangement practices - Alwan, N.; Moss, S. L.; Elliott-Sale, K. J.; Davies, I. G.; Enright, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Physique competitions are events in which aesthetic appearance and posing ability are valued above physical performance. Female physique athletes are required to possess high lean body mass and extremely low fat mass in competition. As such, extended periods of reduced energy intake and intensive training regimens are used with acute weight loss practices at the end of the precompetition phase. This represents an increased risk for chronic low energy availability and associated symptoms of relative energy deficiency in sport, compromising both psychological and physiological health. Available literature suggests that a large proportion of female physique athletes report menstrual irregularities (e.g., amenorrhea and oligomenorrhea), which are unlikely to normalize immediately postcompetition. Furthermore, the tendency to reduce intakes of numerous essential micronutrients is prominent among those using restrictive eating patterns. Following competition, reduced resting metabolic rate, and hyperphagia, is also a concern for these female athletes, which can result in frequent weight cycling, distorted body image, and disordered eating/eating disorders. Overall, female physique athletes are an understudied population, and the need for more robust studies to detect low energy availability and associated health effects is warranted. This narrative review aims to define the natural female physique athlete, explore some of the physiological and psychological implications of weight management practices experienced by female physique athletes, and propose future research directions.